Influence of organization communication on employee’s job motivation and job performance in the broadcast organizations in Delta State, Nigeria - Ugo Chuks Okolie (Journal of Islamic Economics, Management, and Business (JIEMB), 2022)
The core of this study was to examine via inferential and descriptive statistics, the statistical correlation between organization communication on employee’s job motivation and job performance in the broadcast organizations in Delta State, Nigeria. This study was anchored on the unitary theory of industrial relations due to its relevance to the scope of this study. To achieve the general and specific objective of this study, the descriptive survey research design was adopted and primary data were obtained from questionnaire responses administered to one hundred and seventy-one staff of the seven broadcast organizations used for the study. Hypotheses were formulated and tested and findings emerged. This chapter therefore presents the summary of this study’s findings, conclusion, contribution to knowledge and recommendations. The findings revealed that, job motivation indicators has no significant linear relationship with employee job motivation in broadcast organizations in Delta State; job performance indicators has a significant positive linear relationship with employee job performance in broadcast organizations in Delta State; Organizational communication has a significant positive linear relationship with employee job motivation in broadcast organizations in Delta State and that Organizational communication has no significant linear relationship with employee job performance in broadcast organizations in Delta State. The study recommends amongst others that, pay policies and procedures that will enable employers to attract, motivate, retain and satisfy their employees should be developed; employers and management of different industries must find the most crucial factors before implementing their motivational policies; employees that are duly appreciated for satisfactory performance should not take it for granted as it will project their intensions to the employer whether to repeat such good gesture or not.